(untitled) (Global Journal of Medical Research, 2015)
Hypertension is a chronic and end stage disease. The biomolecular mechanism involved in the pathogenesis can be interrupted for improving therapeutic approach and prognosis. identifying the risk factors and causes of hypertension is essential to categorize into idiopathic and secondary hypertension. Garlic used since ancient time has drawn attention for deeper research towards its contribution to various health benefits. Its vital component allicin has played key role in beneficial effects of garlic.